Stages of emergence and development of freestyle wrestling in the West Kazakhstan region of the Republic of Kazakhstan - Sobyanin, F.I.; Isaev, I.F.; Makashev, Sh.A.; Krivchenkov, V.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to substantiate the stages of development of freestyle wrestling in the West Kazakhstan region of the Republic of Kazakhstan. Methods and structure of the study. The work was carried out on the basis of the Belgorod State University and the West Kazakhstan Innovation and Technology University in 2018-2022. We used historical and culturological-acmeological approaches, analysis and generalization of data from special literature, electronic sources, archive documents of the West Kazakhstan region, a survey of trainers, a study of the reporting materials of the department of physical culture and sports of the West Kazakhstan region. Results and conclusions. The most important factors that determine the periodization of the development of freestyle wrestling in the region of the West Kazakhstan region are identified: the effectiveness of the activities of coaches and athletes, the nature of the expansion of the scope of freestyle wrestling in the region, the quantitative composition of coaching staff and their qualifications, scientific, methodological and logistical support, social historical changes in the region, economic provision, demographic dynamics, organizational and managerial activities. As a result of the study, four stages in the development of freestyle wrestling in the region were identified: the stage of the origin and initial development of freestyle wrestling in the West Kazakhstan region; the stage of the spread of freestyle wrestling in the region; stage of intensive development of freestyle wrestling; the stage of reaching the maximum achievements of athletes of the region in freestyle wrestling. The established time periods and the main trends of the stages show the progressive nature of the development of freestyle wrestling in the region.